SINFONI: a high-resolution near-infrared imaging spectrometer for the VLT - Tecza, M; Thatte, N (1998)
The SINFONI1 project combines the MPE cryogenic near-infrared imaging spectrometer SPIFFI2 with an ESO adaptive-optics system on the ESO-VLT to perform high spatial and spectral resolution studies of compact objects. This paper describes the optical design of SPIFFI and the novel techniques used in building its integral-field unit.The image slicer comprises of a bundle of 1024 silica/silica fibers, where each fiber tip is flared to increase the core diameter by a factor of 15. The tapered end is polished to form a spherical microlens with a hexagonal cross-section to couple Light into the optical fiber. This not only yields a high light-coupling efficiency and a high geometrical filling factor but also allows us to use the fiber bundle at a working temperature of 77 K without losing positioning accuracy.